2019
DOI: 10.1101/2019.12.16.876623
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanism ofin vivoactivation of the MutLγ-Exo1 complex for meiotic crossover formation

Abstract: 22Crossovers generated during the repair of programmed double-strand breaks 23 (DSBs) are essential for fertility to allow accurate homolog segregation during the 24 first meiotic division. Most crossovers arise through the asymmetric cleavage of 25 double-Holliday junction (dHJ) intermediates by the MutLγ endonuclease (Mlh1-26 Mlh3) and an elusive non-catalytic function of Exo1, and require the Cdc5/PLK1 27 kinase. Here we show in budding yeast that MutLγ forms a constitutive complex 28 with Exo1, and in meio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…Indeed, homodimers of yeast Mlh1 have been reported, and an increase of their formation can inhibit MMR (74). In addition, in support of a possible heterodimer formation, a recent study in budding yeast found co-immunoprecipitation of Mlh3 with Pms1 (75). The crystal structure of the C-terminal region of human MLH1 (Protein Data Bank code 3RBN) showed that human MLH1 could form homodimers with the same residues involved in the heterodimer formation (14).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, homodimers of yeast Mlh1 have been reported, and an increase of their formation can inhibit MMR (74). In addition, in support of a possible heterodimer formation, a recent study in budding yeast found co-immunoprecipitation of Mlh3 with Pms1 (75). The crystal structure of the C-terminal region of human MLH1 (Protein Data Bank code 3RBN) showed that human MLH1 could form homodimers with the same residues involved in the heterodimer formation (14).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly in Sordaria, MSH4 foci appear in early meiotic prophase than MLH1 foci and the number of MSH4 is higher than that of MLH1 (Storlazzi et al, 2010). Interestingly, a recent study showed a chromosomal localization of a tagged version of Mlh1 in the budding yeast and the number of Mlh1 foci is less than ZMM foci in wild type, supporting a regulatory transition from MutSγ to MutLγ is operating in yeast meiosis (Sanchez et al, 2020).…”
Section: Foci Containing Msh5 Exhibit Homeostasis In Response To Redu...mentioning
confidence: 92%
“…It is not fully understood what kinds of chromosomal architecture or protein–protein interactions are required to stabilize Mlh1–Mlh3 or direct its function (Manhart et al, 2017). There is clear evidence for posttranslational modifications regulating meiotic crossover formation (He et al, 2020; Hollingsworth & Gaglione, 2019; Sanchez et al, 2020; Sourirajan & Lichten, 2008; Wild et al, 2019; Wild & Matos, 2016). For example, the structure‐specific endonucleases Mus81–Mms4 and Yen1 that act in the interference‐independent crossover pathway are activated and inhibited, respectively, by phosphorylation (Figure 1; Matos, Blanco, Maslen, Skehel, & West, 2011; Wild & Matos, 2016).…”
Section: Baker's Yeast Mutl Homolog Proteinsmentioning
confidence: 99%